Development of Agrotourism to Support Tourism Growth in Sigapiton Village - Marpaung, Dinda Yolanda; Dewi Yanti; Muhammad Khadry (International Journal of Travel, Hospitality and Events, 2025)
This research aims to analyze the potential for developing agrotourism in Sigapiton Village as an effort to support rural tourism development. The analysis was carried out using the 6A components approach (Attractions, Accessibility, Amenities, Available Packages, Activities, and Ancillary Services) to identify the strengths and weaknesses of the destination. Furthermore, a SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) was conducted to map internal and external factors influencing agrotourism development. Based on the SWOT results, the QSPM (Quantitative Strategic Planning Matrix) method was used to determine the most effective priority strategies to be implemented. The findings indicate that Sigapiton Village has strong potential in terms of natural beauty, local culture, and agricultural diversity, but still faces challenges such as limited accessibility, lack of public facilities, and low community involvement. Through QSPM calculations, the prioritized strategies identified are: (1) development of educational tourism packages based on agriculture and local culture; (2) improvement of accessibility and public facilities; (3) optimization of the role of the community and youth; and (4) digital promotion and agrotourism branding. These strategies are expected to support the development of tourism in Sigapiton Village as an agrotourism destination and contribute to the well-being of the local community.